Calculation, knowledge, and identity: Dimensions of trust when making COVID-19 vaccination choices in China - Lirui Jiao; Jonas Wachinger; Selina Dasch; Till Bärnighausen; Shannon A. McMahon; Simiao Chen (Elsevier, 2023)
Vaccine hesitancy threatens the response to the COVID-19 pandemic and to other infectious disease outbreaks globally. Fostering trust has been highlighted as a critical factor in addressing vaccine hesitancy and expanding vaccine coverage, but qualitative exploration of trust in the context of vaccination remains limited. We contribute to filling this gap by providing a comprehensive qualitative analysis of trust in the context of COVID-19 vaccination in China.We conducted 40 in-depth interviews with Chinese adults in December 2020. During data collection, trust emerged as a highly salient topic. Interviews were audio-recorded, transcribed verbatim, translated into English, and analyzed with a combination of inductive and deductive coding. Following established trust literature, we differentiate between three types of trust - calculation-based trust, knowledge-based trust, and identity-based trust - which we grouped across components of the health system, as informed by the WHO's building blocks.Our results highlight how participants attributed their level of trust in COVID-19 vaccines to their trust in the medical technology itself (based on assessing risks and benefits or previous vaccination experiences), the service delivery and health workforce (informed by past experiences with health providers and their role throughout the pandemic), and leadership and governance (drawing on notions of government performance and patriotism). Reducing negative impact from past vaccine controversies, increasing the credibility of pharmaceutical companies, and fostering clear communication are identified as important channels for facilitating trust. Our findings emphasize a strong need for comprehensive information on COVID-19 vaccines and increased promotion of vaccination by credible figures.